Best Practices for Intrathecal Drug Delivery for Pain. Issue 4 (21st January 2014) - Prager, Joshua; Deer, Timothy; Levy, Robert; Bruel, Brian; Buchser, Eric; Caraway, David; Cousins, Michael; Jacobs, Marilyn; McGlothlen, Gail; Rauck, Richard; Staats, Peter; Stearns, Lisa
<x xml:space="preserve">Abstract</x> Objective The objective of this study was to identify best practices and provide guidance to clinicians to ensure safety and optimize intrathecal drug delivery for chronic intractable pain. Methods Twelve experienced pain medicine practitioners—eight anesthesiologists, one neurosurgeon, one physiatrist, one clinical psychologist, and one advanced practice registered nurse—from the United States, Australia, and Europe gathered to identify and publish consensus on best practices in three areas related to safe intrathecal therapy for pain: safety and monitoring, patient and device management, and patient selection and trialing. Conclusions Intrathecal drug delivery is a valuable alternative drug delivery system for many patients with severe chronic or end‐of‐life pain. While device‐related complications (mostly with catheters) and surgical‐site infections can occur, the main therapy‐related safety issues associated with intrathecal drug delivery arise primarily with inadequate patient monitoring (e.g., respiratory depression), inflammatory mass (e.g., high doses and concentrations of opioids), wound healing, dosing errors (e.g., medication concentration and pump programming), pump fills or refills (e.g., pocket fills), and interaction with concomitant systemic medications (e.g., opioids and benzodiazepines). Many of the reported adverse events and complications of intrathecal drug delivery can be prevented by adequate clinician training, implementation of best practices, and experience. In adopting the therapy, patients must be apprised of its risks and benefits. Physicians and patients must partner to achieve both safety and effectiveness.